A07 Should Diagnostic Criteria in HD be Changed?. (17th September 2014) - McCusker, E
Abstract : Background: To date motor manifestations, particularly the presence of chorea, a family history and/or mutation carrier status on genetic testing defines a diagnosis of clinical Huntington Disease (HD). Evidence for progression of cognitive and imaging measures ahead of or with motor manifestations in the prodrome has mounted, especially in the major observational studies following mutation carriers through the disease prodrome to definite diagnosis (PREDICT-HD, TRACK-HD). Aims: Outline the reasons for review of the diagnostic criteria in HD, the need for a practical definition of cognitive impairment sufficiently specific for inclusion in revised diagnostic criteria and the impediments to change. Methods: Present case examples and review evidence of cognitive onset reported in studies of the HD prodrome. Outcome: A case exists to change HD diagnostic criteria particularly to allow for cognitive manifestations that result in a predominantly non choreic/non motor phenotype at onset. More inclusive diagnostic criteria are important in clinical trials to capture a better representation of the HD phenotype and for therapeutic interventions including for cognitive and behavioural manifestations. There is support from case studies that if left undiagnosed non choreic HD has much greater impact on function as well as behaviours for which there may be early treatment and care than the initial motor manifestations, currently the basis for diagnosis. Conclusion: With some caveats diagnostic criteria in HD need to be changed.